"Bom estar aqui" - Fotolivro sobre a memória do Programa VIP e a sua influência no fortalecimento da imagem da Universidade Federal do Amazonas - Bentes, Ligia Maciel (Brasil, 2019)
The experimental project, in a booklet format, seeks to safeguard the institutional memory of the Visits Program for the Internal and External Publics of the Federal University of Amazonas, which in this year of 2019, completes more than a decade of existence and provides service to society. Beyond to discussing the influence in the process of strengthening the representation of the University. Accordingly, the research had as theoretical foundation the parameters of the institutional communication, crossing the use of communication vehicles such as photography and guided visits. The methodological resources applied were interviews, collection of statements and analysis of questionnaires, which gathered information that composes the visual narrative of the project. Keywords: